The new books kids like - Deeds, Sharon; Chastain, Catherine (American Library Association, 2001)
With this handy new reference, you'll be equipped to answer questions for young people who know exactly what they want as well as for those who have no idea but just know that they want something ''good.'' Seasoned librarians Deeds and Chastain surveyed children's librarians from around the country, bringing together the wisdom and experiences of librarians from both school and public library settings for one collection of expert picks. Organized around 44 topics considered by the panel to be ''the most frequently requested, '' the end result is chock full of more than 500 annotated book recomm.